The effect of post-exercise heat exposure (passive heat acclimation) on endurance exercise performance: a systematic review and meta-analysis - Thomas P. J. Solomon; Matthew J. Laye (BMC Sports Science, Medicine and Rehabilitation)
Abstract Background “Active” heat acclimation (exercise-in-the-heat) can improve exercise performance but the efficacy of “passive” heat acclimation using post-exercise heat exposure is unclear. Therefore, we synthesised a systematic review and meta-analysis to answer whether post-exercise heat exposure improves exercise performance. Methods Five databases were searched to identify studies including: (i) healthy adults; (ii) an exercise training intervention with post-exercise heat exposure via sauna or hot water immersion (treatment group); (iii) a non-heat exposure control group completing the same training; and (iv) outcomes measuring exercise performance in the heat (primary outcome), or performance in thermoneutral conditions, V̇O2max, lactate threshold, economy, heart rate, RPE, core temperature, sweat rate, and thermal sensations. Study quality was assessed using the Cochrane Risk of Bias 2 tool. To determine the effect of post-exercise heat exposure, between-group ratio of means or standardized mean differences (SMD) were calculated for each outcome and weighted by the inverse of their variance to calculate an overall effect estimate (ratio of mean or Hedges’g) in a random effects meta-analysis, with 95% confidence intervals (CI) and prediction intervals (PI). Quality of evidence was assessed using the Grading of Recommendations Assessment, Development and Evaluation (GRADE) tool. Results Ten studies (199 participants: 156 male, 43 female, age 20–32 years) were included. The effect of post-exercise heat exposure on performance in hot conditions (33–40 °C) was trivial (ratio of means = 1.04) with poor precision (95%CI 0.94–1.15, P = 0.46) and low predictive certainty (95%PI 0.81–1.33). There were also trivial effects on performance in thermoneutral conditions (18–24 °C) and speed at lactate threshold, small effects on V̇O2max, heart rate, core temperature, and sweat rate, and a moderate effect on thermal sensations. However, the certainty in the effect estimates was graded as low to very low across all outcomes due to small sample sizes, high risk of bias, risk of publication bias, imprecision in the effect estimates, and low statistical power. Conclusions The use of post-exercise heat exposure for improving exercise performance is uncertain. Further high-quality trials are needed to make firm conclusions. Protocol registration Open Science Foundation ( https://doi.org/10.17605/OSF.IO/256XZ ).